Poissonova porazdelitev - osnove, uporaba, nadgradnja - Vidmar, Gaj (Informatica Medica Slovenica, 2012)
The tutorial comprehensively introduces the Poisson distribution. It is derived as a limit of the binomial distribution. Its fundamental properties are presented shape, moments, moment generating function and convolution. Examples of its application in spatial and time framework are given, followed by parameter estimation, goodness-of-fit (via statistical tests and graphical methods), the concepts of under- and overdispersion, and a historical overview. The final part of the tutorial briefly presents selected extensions: related distributions; bi- and multivariate Poisson distribution; mixtures of Poisson random variables; a statistical test for comparing two Poisson counts; Poisson regression; and control charts related to the Poisson distribution. The tutorial is accompanied by a comprehensive and detailed interactive workbook in Excel 2007/2010 format.
Keywords: matematika; Poissonova porazdelitev; statistika; verjetnost